Dua Altar dalam Satu Perayaan Ekaristi: Inkulturasi Liturgi Gereja Katolik dalam Misa Dange Umum Masyarakat Dayak Kayan - Maria Magdalena Husun; Yanto Sandy Tjang; Florentina Florentina; Felisitas Yuswanto; Amadi Amadi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the Common Dange Mess at the Parish of Santo Antonius Padua Mendalam as a manifestation of the inculturation of Catholic faith with the Dayak Kayan culture. Using a descriptive qualitative approach, the study focuses on the meaning and relationship between the Church altar and the Lasah as symbols of liturgy and culture. The altar remains the sacramental center of the Eucharist, while the Lasah channels prayers, offerings, and local cultural identity, forming a harmonious dialogue without altering theological meaning. Cultural elements such as language, songs, dances, traditional attire, and ritual symbols are purified and aligned with the liturgy, ensuring that all offerings are directed to God. The findings indicate that the Common Dange Mess strengthens the faith of the Dayak Kayan community, preserves cultural identity, and affirms the practice of contextual theology, in which the proclamation of the Gospel is realized contextually, dialogically, and complementarily with local traditions, making this celebration a mature model of inculturation centered on Christ.